TINJAUAN MAá¹¢LAá¸¤AH TERHADAP PERLINDUNGAN HUKUM BAGI ANAK YANG BEKERJA DI INDONESIA (Ahkam: Jurnal Hukum Islam, 2023)
Labor law still allows children to work with certain restrictions. The existence of working children needs legal protection so that children's rights can still be fulfilled and protected by the State. On the other hand, Islamic law highly upholds and protects children's rights according to the principles of maqashid sharia. The author views that there is a problem between the legal protection and the theory of mashlahah. Therefore, the author tries to find out how far labor law protects children who work in Indonesia and sees this legal protection from the perspective of mashlahah. This research method is normative legal research with a statutory and conceptual approach, which examines secondary data in the form of related laws, concepts and theories. The results of the study show that legal protection for working children in Indonesia includes restrictions on minimum age, working hours, safety and health protection, wages, and limitations on work involving children. The existence of legal protection for working children in Indonesia is included in the mashlahah mulghoh category. Its application is more harmful than giving mashlahah to children. Even though the existence of mashlahah is contrary to syara', the existence of legal protection rules for working children in Indonesia is still needed because working children are still found in society.